2019
DOI: 10.1039/c8em00336j
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigator series: radium accumulation in carbonate river sediments at oil and gas produced water discharges: implications for beneficial use as disposal management

Abstract: In the western U.S., produced water from oil and gas wells discharged to surface water augments downstream supplies used for irrigation and livestock watering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Only radium concentrations decreased with distance downstream, thereby following the trend observed in mutation rates (Table S4; McLaughlin et al, 2020). Radium was also present above the MCL at the discharge (McDevitt et al, 2019). Arsenic, cadmium and lead were not detected at the NPDES discharge but were detected downstream, suggesting that these species were already present in the soil or were concentrated due to evaporation downstream (Table S4; McLaughlin et al, 2020).…”
Section: Yeast Copy Number Variation and Point Mutation Assaysmentioning
confidence: 59%
See 1 more Smart Citation
“…Only radium concentrations decreased with distance downstream, thereby following the trend observed in mutation rates (Table S4; McLaughlin et al, 2020). Radium was also present above the MCL at the discharge (McDevitt et al, 2019). Arsenic, cadmium and lead were not detected at the NPDES discharge but were detected downstream, suggesting that these species were already present in the soil or were concentrated due to evaporation downstream (Table S4; McLaughlin et al, 2020).…”
Section: Yeast Copy Number Variation and Point Mutation Assaysmentioning
confidence: 59%
“…There is little precipitation in the region (average 230 mm/year) (NOAA, 2018) and no additional tributaries. A previous study conducted at this site analyzed 228 Ra/ 226 Ra in water samples which indicated that the discharge was sourced from oil and gas reservoirs and that additional sources of water had minimal to no impact on inorganic chemistry downstream (McDevitt et al, 2019). Additionally, during sampling, no other sources of surface water were observed entering the stream.…”
Section: Site Descriptionmentioning
confidence: 97%
“…Disposal of hazardous waste from petroleum industries by burying them in the ground or dumping them into the sea leads to the possibility of pollution of air, soil, groundwater, surface and sea water, which leads to possible adverse effects on the environment, animals, plants and sh, and thus on the health of man himself. [230][231][232][233][234][235][236][237][238][239][240] Perhaps the most prominent of these forms are: Impact on water. [236][237][238][239][240][241] The extractive oil industry is highly inuential in water as it is reected in groundwater, surface water, rivers, oceans and seas, as a result of the waste generated from the exploration and extraction (drilling uids and waste water), as well as extraction of oil through water injection in order to increase the withdrawal of oil and improve productivity.…”
Section: The Main Forms Of Petroleum Pollution Tenormsmentioning
confidence: 99%
“…[230][231][232][233][234][235][236][237][238][239][240] Perhaps the most prominent of these forms are: Impact on water. [236][237][238][239][240][241] The extractive oil industry is highly inuential in water as it is reected in groundwater, surface water, rivers, oceans and seas, as a result of the waste generated from the exploration and extraction (drilling uids and waste water), as well as extraction of oil through water injection in order to increase the withdrawal of oil and improve productivity. 242 In this way, the water works to remove oil from the porous medium through the separation processes, which keeps oil in the reservoir.…”
Section: The Main Forms Of Petroleum Pollution Tenormsmentioning
confidence: 99%
See 1 more Smart Citation